Design and Research of the Image Processing Unit and Telemetric Equipment for the Laser-Guided Very Short Range Air Defence Systems Field Simulator - Fedaravicius, Algimantas; Jasas, Karolis; Survila, Arvydas; Grimaila, Vitas (Elektronika ir Elektrotechnika, 2023)
In this article, the engineering concept of the laser-guided very short range air defence system field simulator, its structure, and practical use are presented. The possibilities and advantages of the practical use of the equipment developed in tactical exercises and individual training of air defence specialists are shown. The field simulator equipment without invasion and compromising functionality into the combat air defence system has been connected and installed. The simulator performs all required shooting procedures without using combat missiles, target detection, shot execution, and maintaining the target in the sighting lens until its destruction. The field simulator reduces training process expenses and increases its efficiency. In the article, the ground control and onboard control units are presented. The units consist of target detection and its positioning, coordinate defining and data transmission (global positioning system (GPS), personal computer (PC), radio frequency (RF) transceiver), pyrotechnic charge for missile launch simulation, and target destruction devices (e.g., smoke generator), whose operating principles, functional capabilities, and work reliability are ensured on the basis of conducted research. The field simulator, which was created based on synthesising the simulator systems studied, has proven itself in practise.